2018
DOI: 10.1111/jbi.13455
|View full text |Cite
|
Sign up to set email alerts
|

Climate suggests environment‐dependent selection on lizard colour morphs

Abstract: Aim:The maintenance of polymorphisms is often explained by sexual selection.However, natural selection may also constrain morphs to particular locations, causing geographical variation in morph diversity. In many well-known polymorphic organisms in which the relevance of sexual selection on the maintenance of polymorphisms is widely supported, the role of environmental factors has been poorly studied. Here, we adopted a population-level approach to assess the extent to which geographical variation in climate e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 77 publications
4
46
0
Order By: Relevance
“…Most importantly, all of these lizard species share a similar color polymorphism presented as distinct color badges on the throat, suggesting a similar evolutionary origin and function (Stuart-Fox & Ord, 2004). Color polymorphism is common among lacertid lizards, and the lacertid genus Podarcis is highly color polymorphic (Sacchi et al, 2007;Huyghe et al, 2007;Runemark et al, 2010;Pérez i de Lanuza, Sillero & Carretero, 2018). Previous studies of color polymorphic Podarcis species have identified color morph differences in size and survival (Calsbeek, Hasselquist & Clobert, 2010), ability to win staged contests (Huyghe et al, 2012;Abalos et al, 2016), absolute maximum bite force capacity and head muscle mass (Huyghe et al, 2008), and circulating hormone levels associated with aggressive behaviors (Huyghe et al, 2009a;Huyghe et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most importantly, all of these lizard species share a similar color polymorphism presented as distinct color badges on the throat, suggesting a similar evolutionary origin and function (Stuart-Fox & Ord, 2004). Color polymorphism is common among lacertid lizards, and the lacertid genus Podarcis is highly color polymorphic (Sacchi et al, 2007;Huyghe et al, 2007;Runemark et al, 2010;Pérez i de Lanuza, Sillero & Carretero, 2018). Previous studies of color polymorphic Podarcis species have identified color morph differences in size and survival (Calsbeek, Hasselquist & Clobert, 2010), ability to win staged contests (Huyghe et al, 2012;Abalos et al, 2016), absolute maximum bite force capacity and head muscle mass (Huyghe et al, 2008), and circulating hormone levels associated with aggressive behaviors (Huyghe et al, 2009a;Huyghe et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…Further, social interactions among morphs can dictate morph diversity across populations ( Pérez i de Lanuza, Carretero & Font, 2017 ). Thus, the number of morphs and the maintenance of color polymorphism can be the result of natural selection, sexual selection, both natural and sexual selection, and sometimes perhaps even neutral processes ( Gray & McKinnon, 2007 ; Rudh, Rogell & Höglund, 2007 ; Runemark et al, 2010 ; Pérez i de Lanuza, Sillero & Carretero, 2018 ). But across taxa, one thing remains clear: the key to understanding color polymorphism lies in identifying the number of morphs and morph-correlated characteristics and the broader context in which these alternative phenotypes are operating and interacting with each other.…”
Section: Introductionmentioning
confidence: 99%
“…Most available results agree with the hypothesis that sexual selection is important for the maintenance of this polymorphism (Galeotti et al ., ; Pérez i de Lanuza et al ., , , ; Ábalos et al ., ). However, evidence from geographic variation of local morph composition and habitat use by morphs in sympatry suggests that this polymorphism is also environmentally constrained (Pérez i de Lanuza & Carretero, ; Pérez i de Lanuza et al ., ,b).…”
Section: Introductionmentioning
confidence: 99%
“…Colour polymorphism is common among lacertids, some species being currently under intense scrutiny with the aim to test hypotheses for the evolution of polymorphisms (e.g. Carretero et al ., ; Huyghe et al ., , ; Galeotti et al ., ; Pérez i de Lanuza, Font & Carazo, ; San‐José et al ., ; Pérez i de Lanuza, Font & Carretero, ; Pérez i de Lanuza, Carretero & Font, ; Pérez i de Lanuza, Sillero & Carretero, ). A crucial question to properly address the study of colour polymorphisms is whether relevant observers of the polymorphism (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation